Towards Sustainable Future: Adoption Dynamics of Climate-Smart Agriculture by Smallholder Farmers in the Sidaama Region, Ethiopia - Abera Argo Lankamo; Dayanandan Ramalingam; Bantyergu Engida Bati; Samuel Jilo Dira (SAGE Open)
This study examined the adoption of climate-smart agriculture (CSA) technologies and their determinants among smallholder farmers in the Sidaama Region, Ethiopia. A mixed research approach with descriptive and explanatory sequential designs analyzed data from 391 systematically sampled households. A multivariate probit model and logistic regression identified factors influencing adoption. The most adopted CSA technologies were crop diversification (CD), integrated soil fertility management (ISFM), agroforestry (AF), integrated pest management (IPM), and small-scale irrigation (SSI). The CD was the most widely adopted technology. Agroecological zones (AEZs) significantly influenced adoption, with probabilities highest in the midland (95.2%) and lowland (90.8%). Income from crop production emerged as the most consistent driver of CSA adoption. Higher incomes significantly increased adoption, particularly for CD and SSI. The probability of adopting CD approached 100% for incomes above ETB 60,000, while SSI adoption increased from 16.4% at the lowest income to 95.5% at the highest. Training within the past 12 months significantly boosted AF and IPM adoption by 80.8% and 68.4%, respectively. Larger landholdings increased SSI adoption, while higher tropical livestock unit (TLU) levels negatively affected CD and ISFM, possibly due to land fragmentation. Market distance hindered SSI adoption, with probabilities declining from 14.1% at 1.7 km to 10.8% at 2 km. These findings highlight the importance of targeted interventions to enhance CSA adoption, including income diversification, capacity-building training, and improved infrastructure. By addressing these factors, policymakers can promote sustainable agricultural practices tailored to agroecological and socioeconomic contexts, fostering resilience and productivity among farmers in Sidaama.